Asupan Purin Terhadap Kadar Asam Urat Pada Penderita Gout Arthritis Di Wilayah Kerja Puskesmas Ranotana Weru - Henry S. Imbar; Nonce Nova Legi; Jualita Dorace Pinunsanda (POLTEKKES KEMENKES MANADO, 2018)
Gout or gout is a chronic arthritis caused by swelling and usually attacks the big toe. Factors causing gout arthrits are excessive uric acid products, obesity, diabetes accompanied by high blood pressure, excessive protein consumption, sex, and alcohol. The purpose of this study was to determine the relationship between purine intake and uric acid levels in patients with gout arthritis in the Ranotana Weru Public Health Center. The method used in this study uses a cross sectional design on a total of 44 samples. The sample criteria are patients with symptoms of gout arthritis and can communicate well. Research sites in the Ranotana Weru Public Health Center in Manado in 2018. Data on age, sex, and occupation can be obtained through interviews using the informed consent form. Purine intake data can be obtained through interviews with the Semi Food Frequency Questinary (FFQ). Gout criteria are divided into two, namely normal and high bivariate data analysis using the chi square test. The results of research on patients with high uric acid levels are 73% and 27% normal, asupa purin more 68%, 21% enough and less 11%. The conclusion from this study is that there is a chi square test relationship showing that intake of purines has a significant relationship between uric acid levels with a value of p = 0,000 (p = 0.05).